The Influence Of Using Bifidobacterium Germs In The Diet Of Hamster On Coliforms Germs Count (Journal of Hama University, 2020)
Bifidobacterium is one of the first species to colonize the gastrointestinal tract and plays a prominent role in the microbial intestinal balance. It is used in the treatment and prevention of pathogenic microbes and is used as probiotic supplements as well as its clinical properties in the prevention of diarrhea and the prevention of irritable bowel syndrome. The aim of this research was to study the effect of  bifidobacterium germs in three different concentrations on the coliform count. Syrian hamster was used in the experiment where the animals were randomly distributed in four different groups (n = 5). group 1: no milk was given, group 2: the concentration was given at 105 cfu / ml milk, group 3: was given the concentration of 107 cfu / ml of milk, group 4: given the concentration of 109 cfu / ml milk.The experiment was conducted for 4 weeks during which the milk was given at different concentrations to the hamster, then the stool was collected at the end of each week and the saline solution was added by concentration 0.9%. Then they are selectively cultured on MRS Agar for selective isolation of  bifidobacterium and VRB Agar is used for selective isolation of coliform bacteria. The count of bifidobacterium began to rise at the end of week 1 and continued to rise until the end of week 4 while the count of coliform bacteria began to decrease at the end of week 2 and continued to decrease until the end of the week 4. After the analysis of the data, the best concentration of milk was found to be 107 cfu / ml milk, where the count rate at the end of week 4 increased to 8.60 ±0.32  log10 cfu/ g  and decreased coliform count at the end of the week 4 (P < 0.05), As well as the best increase in weight at the end of the week 4 (105±3.16) g average hamster weight. The histological study showed an increase in the length and thickness of the intestinal villi and increase mucous, and  goblet cells.